'Muzzas' and 'Old Skool Ravers': Ethnicity, drugs and the changing face of Melbourne's dance party/club scene - Siokou, Christine; Moore, David; Lee, H. (The Australian Sociological Association, 2010)
The relationship between ethnicity and the use of 'party drugs' (e.g., methamphetamine and ecstasy) has received little attention in Australia. This paper focuses on ethnicity and party drug use within the context of dance parties and clubs in Melbourne, Australia's second largest city. The young people who participated in our research, many of whom are long-time dance party attendees, or 'old skool ravers', frequently made claims to the possession of subcultural capital by labelling as 'muzzas' those they perceived to be outsiders to the dance scene. Muzzas are defined as heavily muscled young men, commonly of Southern European or Middle Eastern background, who use cocaine and steroids, have 'no class' and dance in an overly aggressive way. Although the old skool ravers were often from similar ethnic backgrounds to muzzas, they rarely drew on ethnicity in forming their own identities. They did, however, explicitly invoke ethnicity in the distinctions they created between themselves and muzzas. Their claims to subcultural capital are based on notions of nostalgia and an authentic involvement in the dance scene, and on their perceived distance from a mainstream culture consisting of 'normal people'.